Extreme duration exercise affects old and younger men differently. (18th April 2022) - Frandsen, Jacob; Sahl, Ronni Eg; Rømer, Tue; Hansen, Mikkel Thunestvedt; Nielsen, Andreas Blaaholm; Lie‐Olesen, Michelle Munk; Rasmusen, Hanne Kruuse; Søgaard, Ditte; Ingersen, Arthur; Rosenkilde, Mads; Westerterp, Klaas; Holst, Jens Juul; et al.
Abstract: Aim & Methods: Extreme endurance exercise provides a valuable research model for understanding the adaptive metabolic response of older and younger individuals to intense physical activity. Here, we compare a wide range of metabolic and physiologic parameters in two cohorts of seven trained men, age 30 ± 5 years or age 65 ± 6 years, before and after the participants travelled ≈3000 km by bicycle over 15 days. Results: Over the 15‐day exercise intervention, participants lost 2–3 kg fat mass with no significant change in body weight. V̇O2 max did not change in younger cyclists, but decreased ( p  = 0.06) in the older cohort. The resting plasma FFA concentration decreased markedly in both groups, and plasma glucose increased in the younger group. In the older cohort, plasma LDL‐cholesterol and plasma triglyceride decreased. In skeletal muscle, fat transporters CD36 and FABPm remained unchanged. The glucose handling proteins GLUT4 and SNAP23 increased in both groups. Mitochondrial ROS production decreased in both groups, and ADP sensitivity increased in skeletal muscle in the older but not in the younger cohort. Conclusion: In summary, these data suggest that older but not younger individuals experience a negative adaptive response affecting cardiovascular function in response to extreme endurance exercise, while a positive response to the same exercise intervention is observed in peripheral tissues in younger and older men. The results also suggest that the adaptive thresholds differ in younger and old men, and this difference primarily affects central cardiovascular functions in older men after extreme endurance exercise.